Voicing the Students' Need of English Vocabulary English for Specific Purposes in Vocational High School - Maulani, Dwi Siska; Friatin, Lilies Youlia; Rachmawati, Etika (Journal of Education, Language Innovation, and Applied Linguistics, 2022)
The goal of this study was to identify the English vocabulary requirements for agriculture students. The purpose of this study is to find out what students think about the importance of English vocabulary for agriculture students. The qualitative case study design was used in this investigation. This study was undertaken at a Tasikmalaya vocational school with a horticulture major. The researchers employed an open-ended questionnaire to collect data from twenty-one participants, including one English teacher and twenty agricultural students in the horticulture major. The researcher evaluated and interpreted the results of the open-ended questionnaire. When conducting analysis, the researcher assigns a code to each participant's response, organizes the data, and finally obtains the questionnaire's conclusion. The findings of an open-ended questionnaire based on students’ perceptions revealed that agricultural vocabulary is important for some areas, such as English for agriculturists, animal breeders, and in some fields of agriculture, such as cultivating the plants, care the plants, agricultural equipment, or scientific names of plants because learning English vocabulary can increase students' knowledge, particularly specific vocabulary, as well as learning English vocabulary for ag. Finally, the researchers make recommendations on how to better meet the demands of vocational students, particularly in terms of the English vocabulary required of agriculture students. Keywords: English for Specific Purposes; English Vocabulary; Voicing; Students’ Need; Vocational High School.